Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapters 1-5 Cumulative Review Problem Set - Page 233: 16



Work Step by Step

We will evaluate the expression by first simplifying the expression and then substituting $n=3$ into the resultant expression: $2(n^{2}-3n-1)-(n^{2}+n+4)-3(2n-1)$ =$2n^{2}-6n-2-n^{2}-n-4-6n+3$ =$2n^{2}-n^{2}-6n-n-6n+3-2-4$ =$(2n^{2}-n^{2})+(-6n-n-6n)+(3-2-4)$ =$n^{2}-13n-3$ =$(3)^{2}-13(3)-3$ =$9-39-3$ =$-30-3$ =$-33$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.